2021
DOI: 10.3389/fpls.2020.618675
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Litter Decomposition and Nutrient Dynamics to Nitrogen Addition in Temperate Shrublands of North China

Abstract: Plant litter decomposition is a crucial ecosystem process that regulates nutrient cycling, soil fertility, and plant productivity and is strongly influenced by increased nitrogen (N) deposition. However, the effects of exogenous N input on litter decomposition are still poorly understood, especially in temperate shrublands, which hinders predictions of soil C and nutrient dynamics under the context of global change. Temperate shrub ecosystems are usually N-limited and particularly sensitive to changes in exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Litter decomposition plays a crucial role in determining ecosystem function (Chen et al, 2021 ; Zhang et al, 2021 ). It is an important link in the material cycle and nutrient flow that can continuously provide resources to the soil and plants (Scheffer and Aerts, 2000 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Litter decomposition plays a crucial role in determining ecosystem function (Chen et al, 2021 ; Zhang et al, 2021 ). It is an important link in the material cycle and nutrient flow that can continuously provide resources to the soil and plants (Scheffer and Aerts, 2000 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the higher N in litter will contribute to promoting decomposition and therefore result in more rapid N returns to soils (Huang et al, 2008). However, during the late stage of decomposition, N deposition may inhibit the synthesis of ligninolytic enzymes, and reactions with lignin degradation products can form more recalcitrant complexes, then slow late‐stage decomposition (Gill et al, 2021); thus, overall decomposition rates can be slowed (Berg, 2014; Chen et al, 2013; Liu, Huang, et al, 2010) or not affected (Zhang et al, 2021). This phenomenon should weaken or even reverse the positive feedback between litter N and rates of soil N cycling (Berg, 2014; Hobbie, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As compared to other components, leaves and reproductive parts with high N concentration showed fast decomposition. Previous studies (Lv et al, 2013;Zhang et al, 2021) slow decomposing litter. However, high N concentration and slow decomposition rate recorded for components like fine and lateral roots suggested that higher N concentration is not the only criteria that determine the rate of decomposition (Tu et al, 2014;Zhu et al, 2016;Zhang et al, 2021).…”
Section: Controlling Factorsmentioning
confidence: 96%
“…Previous studies (Lv et al, 2013;Zhang et al, 2021) slow decomposing litter. However, high N concentration and slow decomposition rate recorded for components like fine and lateral roots suggested that higher N concentration is not the only criteria that determine the rate of decomposition (Tu et al, 2014;Zhu et al, 2016;Zhang et al, 2021). Other decomposition studies (Silveira et al, 2011) also indicated that the decomposition of plant litter was related more to initial C quality, such as lignin concentration and acid-soluble carbohydrates than to the relative availability of N. Significant (p < 0.01) inverse linear relationship between N and P concentration in residual material and percent weight remaining for all components was observed (Table 7).…”
Section: Controlling Factorsmentioning
confidence: 96%